Impact of Economic and Non-Economic factors on Women Empowerment in India- A study in north coastal Districts of Andhra Pradesh - Dr. Sivasankar Mandal Baidya, . Dr. K. Geetanjali, Shaik Shabana Azmi, A. Maruthi, Dr. P. Jayalakshmi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The national policy for empowerment of women (NPEW) was formulated with an aim about women’s advancement, development and empowerment. The Government of India has declared 2001 as women’s empowerment year Women are the most important real resources to ensure any nation’s development. In the words of our Prime Minister Narendra Modi sir , “empowering women tantamount to empowering the entire family.”